Spectrum of clinical features associated with interstitial chromosome 22q11 deletions: a European collaborative study. Issue 10 (October 1997) - Ryan, A K; Goodship, J A; Wilson, D I; Philip, N; Levy, A; Seidel, H; Schuffenhauer, S; Oechsler, H; Belohradsky, B; Prieur, M; Aurias, A; Raymond, F L; et al.
Abstract : We present clinical data on 558 patients with deletions within the DiGeorge syndrome critical region of chromosome 22q11. Twenty-eight percent of the cases where parents had been tested had inherited deletions, with a marked excess of maternally inherited deletions (maternal 61, paternal 18). Eight percent of the patients had died, over half of these within a month of birth and the majority within 6 months. All but one of the deaths were the result of congenital heart disease. Clinically significant immunological problems were very uncommon. Nine percent of patients had cleft palate and 32% had velopharyngeal insufficiency, 60% of patients were hypocalcaemic, 75% of patients had cardiac problems, and 36% of patients who had abdominal ultrasound had a renal abnormality. Sixty-two percent of surviving patients were developmentally normal or had only mild learning problems. The majority of patients were constitutionally small, with 36% of patients below the 3rd centile for either height or weight parameters.